2016
DOI: 10.5127/jep.057116
|View full text |Cite
|
Sign up to set email alerts
|

A Bi-Factor Approach to Modeling the Structure of Worry and Rumination

Abstract: It remains unclear whether worry and rumination represent the same functional process, or if they are unique constructs. The current study examined the relationship between worry and rumination, focusing on the potential utility of a bi-factor approach as an alternative to "common" vs. "distinctive" approaches. The results indicated that the structural relationship between worry and rumination is best represented by a bi-factor model (compared to singlefactor and two-factor models), which is comprised of a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 44 publications
(90 reference statements)
6
38
1
Order By: Relevance
“…These results concur with those of previous studies (Arditte et al, 2016;Hur et al, 2017;McEvoy and Brans, 2012;Topper et al, 2014) and our own cross-sectional study of the same participants at T6 showing that the common dimension of RNT was significantly associated with each of the depressive and anxiety disorders, comorbidity among depressive and among anxiety disorders, as well as the common core of depressive, anxiety and avoidance symptoms (Spinhoven et al, 2015). However, in contrast to the rather large cross-sectional relations in our previous study (>.50), the prospective relations in the present study had a small effect size (<.30).…”
Section: Discussion Of Research Findingssupporting
confidence: 83%
See 4 more Smart Citations
“…These results concur with those of previous studies (Arditte et al, 2016;Hur et al, 2017;McEvoy and Brans, 2012;Topper et al, 2014) and our own cross-sectional study of the same participants at T6 showing that the common dimension of RNT was significantly associated with each of the depressive and anxiety disorders, comorbidity among depressive and among anxiety disorders, as well as the common core of depressive, anxiety and avoidance symptoms (Spinhoven et al, 2015). However, in contrast to the rather large cross-sectional relations in our previous study (>.50), the prospective relations in the present study had a small effect size (<.30).…”
Section: Discussion Of Research Findingssupporting
confidence: 83%
“…These results are in accordance with most previous cross-sectional studies using a "distinctive" approach showing that rumination is most strongly associated with MDD and worry with GAD, although elevated across disorders (Olatunji et al, 2010;Olatunji et al, 2013). Critically, previous crosssectional studies examining both common and unique aspects of RNT also found an association of unique variance in rumination or brooding with depression (McEvoy and Brans, 2012;Segerstrom et al, 2000;Spinhoven et al, 2015) and unique variance in worry with anxiety outcomes (Hur et al, 2017;Spinhoven et al, 2015) (but see Topper (Topper et al, 2014) for an exception). However, the prospective associations of the unique aspects of RNT may be confounded by content-or disorder-specific depression and anxiety items included in our measures of rumination and worry inflating relations with specific disorders (McEvoy et al, 2013).…”
Section: Discussion Of Research Findingssupporting
confidence: 81%
See 3 more Smart Citations